Activity of ceftizoxime combined with gentamicin against 100 clinical isolates of Pseudomonas aeruginosa. - King, J W (1984)
The effects of ceftizoxime and gentamicin alone and in combination were determined against 100 Pseudomonas aeruginosa strains. Concentrations of 32 micrograms of ceftizoxime and 8 micrograms of gentamicin per ml inhibited 22 and 43% of the strains, respectively. At concentrations of ceftizoxime and gentamicin that are readily achievable in serum, 15 strains were affected synergistically and 17 strains were affected antagonistically. Gentamicin accounted for most of the anti-P. aeruginosa activity of ceftizoxime-gentamicin combinations.